In practice’s practice... you and me within popular education (2015)
This article presents the situation of public education (its current problems) and proposes how collectively “you and I” should rebuild popular education: one in which learning is contextualized and tools are taken to achieve the goals. It is through social practices, in team working, being aware of the core problem, and resuming the importance of reading and writing, the way to a suitable public education for the group we belong to.